Solidification pathway induced microstructural differences in austenitic stainless steels produced by L-PBF - C. Sofras; J. Čapek; G. Soundarapandiyan; A. Baganis; A. Özsoy; M. Šmíd; M. Jambor; N. Casati; C. Leinenbach; S. Van Petegem; M. Strobl; R. E. Logé; et al. (Materials Research Letters, 2025)
This study examines the influence of small compositional variations on the microstructure of 304L stainless steel produced by Laser Powder Bed Fusion (L-PBF). Despite identical processing parameters, N-atomized powder forms textured, columnar grains with elemental segregation, solidifying primarily as γ-austenite with secondary ferrite. In contrast, Ar-atomized powder produces equiaxed grains with uniform composition, following a primary ferrite to secondary γ-austenite mode. Operando synchrotron X-ray diffraction during L-PBF reveals that solidification mode critically shapes the final microstructure, underscoring the importance of solidification control for tailoring properties in austenitic stainless steels.